2018
DOI: 10.1136/bmjopen-2017-020991
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotics for uncomplicated skin abscesses: systematic review and network meta-analysis

Abstract: ObjectiveTo assess the impact of adjunctive antibiotic therapy on uncomplicated skin abscesses.DesignSystematic review and network meta-analysis.Data sourcesMedline, Embase, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov.Study selectionA BMJ Rapid Recommendation panel provided input on design, important outcomes and the interpretation of the results. Eligible randomised controlled trials (RCTs) included a comparison of antibiotics against no antibiotics or a comparison of different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 40 publications
(62 reference statements)
2
26
0
2
Order By: Relevance
“…They requested a systematic review on the benefits and harms of different antibiotics to inform the recommendation. 15 The panel then met online to discuss the evidence and to formulate specific recommendations. As with all BMJ Rapid Recommendations, no panel member had financial conflicts of interest; intellectual and professional conflicts were minimised and managed (see appendix 1 on bmj.com).…”
Section: Current Understandingmentioning
confidence: 99%
See 2 more Smart Citations
“…They requested a systematic review on the benefits and harms of different antibiotics to inform the recommendation. 15 The panel then met online to discuss the evidence and to formulate specific recommendations. As with all BMJ Rapid Recommendations, no panel member had financial conflicts of interest; intellectual and professional conflicts were minimised and managed (see appendix 1 on bmj.com).…”
Section: Current Understandingmentioning
confidence: 99%
“…To inform the recommendations, the guideline panel requested a systematic review of randomised controlled trials (RCTs) on the effects of adjuvant antibiotic therapy compared with no antibiotic therapy in addition to incision and drainage in patients with uncomplicated skin abscesses. 15 …”
Section: The Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…Incision and drainage is the primary therapeutic modality for soft tissue abscesses. A recently published systematic review found that for uncomplicated abscesses, adjunctive antibiotic therapy provides a modest benefit in terms of treatment success and prevention of recurrence, 26 but this needs to be balanced against an increased risk of adverse events. Antibiotic courses ranged from 3-14 days and no recommendation on duration was made.…”
Section: Skin and Soft Tissue Infectionsmentioning
confidence: 99%
“…Antibiotic courses ranged from 3-14 days and no recommendation on duration was made. 26 A randomised controlled trial conducted in the remote Australian setting showed that short-course oral trimethoprim/sulfamethoxazole for 3-5 days is effective for impetigo, and equivalent to intramuscular benzathine penicillin. 27…”
Section: Skin and Soft Tissue Infectionsmentioning
confidence: 99%